Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fendo.2018.00241
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone-Related Protein Negatively Regulates Tumor Cell Dormancy Genes in a PTHR1/Cyclic AMP-Independent Manner

Abstract: Parathyroid hormone-related protein (PTHrP) expression in breast cancer is enriched in bone metastases compared to primary tumors. Human MCF7 breast cancer cells “home” to the bones of immune deficient mice following intracardiac inoculation, but do not grow well and stain negatively for Ki67, thus serving as a model of breast cancer dormancy in vivo. We have previously shown that PTHrP overexpression in MCF7 cells overcomes this dormant phenotype, causing them to grow as osteolytic deposits, and that PTHrP-ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 38 publications
7
25
0
Order By: Relevance
“…Overexpression of PTHrP in otherwise dormant human MCF7 breast cancer cells results in aggressive colonization and osteolysis of the bone through enhanced osteoclastogenesis . PTHrP overexpression in breast cancer cells also reduces pro‐dormancy gene expression, suggesting that PTHrP may play a role in tumor cell exit from dormancy . Further, the enabling of dormant tumor cells to aggressively colonize the bone following PTHrP overexpression appears to be independent of parathyroid hormone receptor type I (PTH1R) and cAMP‐mediated signaling and may rely on the calcium signaling pathway …”
Section: Metastatic Outgrowthmentioning
confidence: 99%
“…Overexpression of PTHrP in otherwise dormant human MCF7 breast cancer cells results in aggressive colonization and osteolysis of the bone through enhanced osteoclastogenesis . PTHrP overexpression in breast cancer cells also reduces pro‐dormancy gene expression, suggesting that PTHrP may play a role in tumor cell exit from dormancy . Further, the enabling of dormant tumor cells to aggressively colonize the bone following PTHrP overexpression appears to be independent of parathyroid hormone receptor type I (PTH1R) and cAMP‐mediated signaling and may rely on the calcium signaling pathway …”
Section: Metastatic Outgrowthmentioning
confidence: 99%
“…PTHrP was originally discovered as the factor that causes humoral hypercalcemia of malignancy and is well established to promote tumor‐induced bone destruction through its stimulation of RANKL on osteoblast lineage cells to promote osteoclast‐mediated bone resorption . More recently, it has been suggested that PTHrP may also play a role in the awakening of tumor cells in the bone marrow . Overexpression of PTHrP, which normally binds to the parathyroid hormone receptor type 1 (PTHR1) to induce cAMP signaling, induces osteolytic bone destruction in cells that otherwise lie dormant in the bone marrow and down‐regulates a number of pro‐dormancy genes through a cAMP‐independent mechanism .…”
Section: Factors Controlling Dormancy or Reactivationmentioning
confidence: 99%
“…More recently, it has been suggested that PTHrP may also play a role in the awakening of tumor cells in the bone marrow . Overexpression of PTHrP, which normally binds to the parathyroid hormone receptor type 1 (PTHR1) to induce cAMP signaling, induces osteolytic bone destruction in cells that otherwise lie dormant in the bone marrow and down‐regulates a number of pro‐dormancy genes through a cAMP‐independent mechanism . Interestingly, PTHrP is regulated by the bone matrix itself, in that tumor cells that come in contact with the rigid bone surface up‐regulate PTHrP; however, this is specific for tumor cells that are already aggressive in nature .…”
Section: Factors Controlling Dormancy or Reactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone-DTCs secrete factors (e.g., parathyroid-hormone-related protein (PTHrP)) that stimulate the receptor activator of NF-κB (RANK)-RANK ligand (RANKL) axis and promote osteoclastogenesis [4]. These factors may enable tumor cells to overcome quiescence [5], but it remains unclear whether some breast cancer cells begin secreting these factors prior to dissemination or during circulation, or whether the bone microenvironment induces breast cancer cells to stimulate osteoclasts. Increased osteoclastogenesis gives rise to localized bone resorption and the release of cytokines and growth factors from the bone matrix that stimulate tumor cell growth and further enhance the RANK-RANKL signaling cascade to promote bone resorption [4], resulting in overt tumor-induced bone disease.…”
Section: Introductionmentioning
confidence: 99%